Pemenuhan Hak Anak Korban Tindak Pidana Perdagangan Orang - Andi Jefri Ardin; Beniharmoni Harefa (Jurnal Suara Hukum, 2021)
One of the most important in human trafficking is the handling of victims. By normative research methods, it discusses the fulfillment of the rights of children who are vulnerable to becoming victims. There are two legal instruments in handling child as victims, there are Law Number 21 of 2007 and Law Number 35 of 2014. Based on the research, the Law Number 21 of 2007 more fulfilling than Law Number 35 of 2014. Government Regulation Number 43 of 2017 as implementing regulations for Law Number 35 of 2014 is not much different in substance from Law Number 21 of 2007. The application of the principle of the right to life and development of children also implies the state's obligation to ensure that children must have all the necessary access like social services, physical and mental health services and education.  Law Number 21 of 2007 nor Law Number 35 of 2014, not fulfilled these principles, for example regarding the education of child as victims. The law enforcement officials must pay attention to the Law Number 8 of 2010, to ensure that the defendant through confiscation of assets can fulfill the restitution for the victims during the investigation process.